Novel Bapak, Kapan Kita Akan Berdamai? Karya Regza Sajogur: Kajian Psikologi Sastra - Gallu Moni, Yunita; Nama, I Ketut; Jumadiah, Sri (Humanis; Vol 21 No 1 (2017), 2017)
The object of this research is the novel Bapak, Kapan Kita Akan Berdamai?. This research is motivated by psychological phenomenon of post traumatic stress disorder (PTSD) on Marolop character. The theory used in the research is the structural theory of Burhan Nurgiyantro, and the theory of literary psychology of Albertine Minderop, Endraswara, and Wahyudi Siswanto, as well as the theory of post traumatic stress disorder namely Emotional and psychological trauma: causes, symptomps, effects, andtreatment of Jaffe. Stuctural theory explains the object of research in three intrinsic elements, namely: characterization, plot, and background. The theory of literary psychology explains several theories related to some psychological psychological theories into this research, namely: the theory of personality structure of psychoanalysis and PTSD theory. The formulation of the problem to be discussed consists of two, namely: structural analysis which includes, characterization, plot, and background, and PTSD phenomena on Marolop. The purpose of this research is to know the novel structure of BKKAB in terms of characterization, plot, and background, and PTSD phenomenon on Marolop. Methods and techniques used in this study there are three, namely: (1) methods and techniques of data collection, used library methods and techniques used is the technique of reading, record; (2) methods and techniques of data analysis used descriptive analysis method, followed by reading and listening techniques; (3) methods and techniques of presenting the results of data analysis described in the format of writing a good and correct thesis. Analysis structure according to Nurgiyantoro cover three aspects namely, characterization, plot and background. Based on the analysis of the psychoanalytic personality structure associated with PTSD, the characters in the BKKAB novel affect each other psychically between one character and another. In the PTSD figures forming a linkage that is, Marolop as victims of physical abuse, the father as the perpetrator, and the mother as a unifier.